Pengendalian dan Pencegahan Komplikasi Hipertensi pada Lansia Melalui Pendidikan Kesehatan Perilaku Patuh dan Teknik Relaksasi Otot Progresif - Mila Triana Sari; Miko Eka Putri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Hypertension is still a major problem in the world, both in developed and developing countries, including Indonesia. Based on Riskesdas 2018 data, there was an increase in hypertension cases by 34.1%, especially in the elderly group, and for Muaro Jambi district, especially Muaro Kumpeh district, it is the no. 2 disease after ARI. Hypertension is nicknamed the Silent killer because it does not show symptoms, so it is necessary to carry out treatment to control hypertension and prevent complications early. The purpose of this community service activity is to increase understanding for the elderly about hypertension and things that can aggravate the condition of hypertension, the importance of obedient behavior and complementary therapy, namely progressive muscle relaxation techniques to control and control hypertension. The implementation of the activity begins with a pre-test, giving material, demonstration of progressive muscle relaxation techniques, post test and ends with a blood pressure check. The result of this activity is that the elderly's knowledge about the control and prevention of hypertension complications was obtained by most of the elderly's knowledge lacking (57.2%) before the activity and the majority of the elderly's knowledge was good (45.7%) after health education activities. It is necessary to carry out health education on an ongoing basis and intensify physical activity progressive muscle relaxation techniques at least 3 times a day to control blood pressure in elderly people with hypertensionso as to realize a better quality of life